Greening Ricardo: Environmental comparative advantage and the environmental gains from trade - Mathilde Le Moigne; Simon Lepot; Ralph Ossa; Marcos Ritel; Dóra Zsuzsanna Simon (World Trade Organization (WTO), 2024)
We show that climate policy can unlock large environmental gains from trade by inducing economies to specialize according to their environmental comparative advantage. We make this point by exploring the effects of a carbon tax in a quantitative trade model. Our main result is that the environmental gains from trade account for over one-third of the total reduction in greenhouse gas emissions brought about by the carbon tax. This finding holds for a wide range of carbon tax rates and coverages.
Keywords: 330